Musical training, individual differences and the cocktail party problem. - Patel, Aniruddh D.; Swaminathan, Jayaganesh.; Mason, Christine R.; Streeter, Timothy M.; Best, Virginia.; Kidd, Gerald D. (Tufts University. Tisch Library., 2016)
Are musicians better able to understand speech in noise than non-musicians? Recent findings have produced contradictory results. Here we addressed this question by asking musicians and non-musicians to understand target sentences masked by other sentences presented from different spatial locations, the classical 'cocktail party problem' in speech science. We found that musicians obtained a substantial benefit in this situation, with thresholds ~6 dB better than non-musicians. Large individual differences in performance were noted particularly for the non-musically trained group. Furthermore, in different conditions we manipulated the spatial location and intelligibility of the masking sentences, thus changing the amount of 'informational masking' (IM) while keeping the amount of 'energetic masking' (EM) relatively constant. When the maskers were unintelligible and spatially separated from the target (low in IM), musicians and non-musicians performed comparably. These results suggest that the characteristics of speech maskers and the amount of IM can influence the magnitude of the differences found between musicians and non-musicians in multiple-talker "cocktail party" environments. Furthermore, considering the task in terms of the EM-IM distinction provides a conceptual framework for future behavioral and neuroscientific studies which explore the underlying sensory and cognitive mechanisms contributing to enhanced "speech-in-noise" perception by musicians.